2012
DOI: 10.1186/1476-9255-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of TLR4 by recombinant HSP70 requires structural integrity of the HSP70 protein itself

Abstract: BackgroundToll-like receptor 4 (TLR4) is activated by bacterial endotoxin, a prototypical pathogen-associated molecular pattern (PAMP). It has been suggested that TLR4 can also be activated by damage-associated molecular pattern (DAMP) proteins such as HSP70. It remains a challenge to provide unequivocal evidence that DAMP proteins themselves play a role in TLR4 activation, as the DAMP proteins used are often contaminated with endotoxin and other TLR ligands introduced during protein expression and/or purifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
(12 reference statements)
1
19
0
Order By: Relevance
“…HSP70, through the stimulation of TLR2 and TLR4 and the activation of MyD88/NF-kB pathways, induces this cytokine production [137]. Similar results were obtained by Luong et al [138]. They found that the ligation of HSP70 with TLR4 leads to increased concentration of TNF-a.…”
Section: Hspssupporting
confidence: 76%
“…HSP70, through the stimulation of TLR2 and TLR4 and the activation of MyD88/NF-kB pathways, induces this cytokine production [137]. Similar results were obtained by Luong et al [138]. They found that the ligation of HSP70 with TLR4 leads to increased concentration of TNF-a.…”
Section: Hspssupporting
confidence: 76%
“…DAMPs are molecules with defined intracellular functions, but outside of the cell, DAMPs are proinflammatory mediators. Examples of such DAMPs include high-mobility group box 1 (HMGB1), a nonhistone nuclear protein (Ciucci et al, 2011; Tang et al, 2011); HSP70, a chaperon protein (Andocs et al, 2015; Luong et al, 2012); fragments of cell-free DNA (Girard et al, 2014; Nadeau-Vallée et al, 2016; Phimister and Phillippe, 2014); telomere fragments (Polettini et al, 2015); and uric acid (Mulla et al, 2011). DAMPs are often recognized by pattern recognition receptors (PRRs) that are located in the cell membranes (Santoni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral CD14+ blood monocytes were purified from healthy whole blood donors using Ficoll density gradient and highly specific monocyte isolation kit (CD14+ antibody magnetic labeled beads, Miltenyii). Proteinase K digestion of flagellin and profilin were performed as described previously [5,6]. Briefly, proteinase K-agarose was reconstituted in endotoxin-free water to 10 mg/mL, incubated at 4°C for 2 hr, and washed five times with endotoxin-free water.…”
Section: Methodsmentioning
confidence: 99%